New insight into migration patterns of western North Pacific humpback whales between the Babuyan Islands, Philippines and the Commander Islands, Russia - Silberg, J. N; Acebes, J. M. V; Burdin, A. M.; Mamaev, E. G.; Dolan, K. C.; Layusa, C. A.; Aca, E. Q. (J. Cetacean Res. Manage., 2023)
The population structure of humpback whales (Megaptera novaeangliae) in the North Pacific has received significant attention in recent years through the collaborative Structure of Populations, Levels of Abundance, and Status of Humpback whales in the North Pacific (SPLASH) study. However, the analysis of humpback whales in the western North Pacific Asian population was limited in the SPLASH study, due to small sample size. Much of the Asian population summers off Kamchatka, Russia and spends the winters in breeding grounds in Okinawa and Ogasawara, Japan and the Babuyan Islands in the northern Philippines. Prior studies grouped the Commander Islands feeding ground in Russia, with the eastern Aleutian Islands as part of the central humpback whale stock. This paper uses additional years of photo-ID data from both the Philippines (160 whales from 2000–12) and the Commander Islands (531 whales from 2008–10) to establish a previously unreported migratory connection by matching four animals between the two sites. The new migratory linkage found in the present study suggests that a small portion of humpback whales hypothesised to be migrating to a ‘missing’ breeding ground in the central North Pacific are actually migrating to the Philippines. However, additional studies on a wider geographical scale are required.